Oh, that cocoa juice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Here's yet another way to get more by-products out of cocoa. Did you know that from the pulp of the fruit you could make delicious refreshing drinks, jam, jellies, wine, and vinegar? This can be a way to make some more money during the cocoa harvest...